Por uma análise da argumentação da força normativa e constitucionalidade do princípio da presunção da inocência na legislação e jurisprudência brasileiras - Nascimento, Tainara Maria Quirino do (2022)
The Brazilian Federal Supreme Court, since 2009, has been changing its jurisprudence about the principle of presumption of innocence, consecutively, changing the argumentation to guarantee a bigger or smaller scope to this principle. In 2009, through the Habeas Corpus no. 84.078, the Supreme Court created the precedent, with this broad discussion, trying to stabilize the decisions which discussed the moment when it would be possible to deprive the freedom of locomotion of an individual: before or after the decision of a second instance court. At the time, the judges, by majority, attributed literal interpretation to the principle of presumption of innocence, establishing that the prison would only be possible after the final judgement of the case. The precedent subsisted for almost seven years, but it was brought to discussion again in 2016, through another Habeas Corpus. In the Habeas Corpus no. 126.292, the majority decided that a different interpretation should be taken, referring, most of the times, that the literal interpretation was conducive to allowing the prescription of the crime without due punishment to the defendant, due to the slow process time. Ultimately, because of unstable controversy during these years, the National Ecological Party decided to raise, through the concentrated control of constitutionality, the constitutional compatibility of Article 283 from the criminal procedural code, which also provides the possibility of prison only after the res judicata. In this discussion, the judges declared that the Article is constitutional. The majority said that the moment when the prison is permitted is only after the res judicata. The « Car Wash » operation also gained attention when it gave elements that subsidized the discussion about the possible disrespect to the principle of presumption of innocence in a procedure which pursued, primarily, investigate and fight corruption. In this work, it was brought some aspects that provoked discomfort on the doctrine of criminal procedure law, which were taken as illegals or, at least, irregulars, in the eyes of the procedure criminal law. At the end, an argumentative balancing was carried out about the discussions that can significate disrespect to the principle of the presumption of innocence, specially using the work of Friedrich Müller e Manuel Atienza. Through the cited doctrine, it was tried to come to the conclusion that inoperative and unenforceable argumentations by the point of view of logical theory of argumentation and investigation of execution of unconstitutional procedures were utilized.